1997
DOI: 10.3102/10769986022003249
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection Information Criteria for Non-Nested Latent Class Models

Abstract: Latent class models have been developed for assessment of hierarchic relations in scaling and behavioral analysis. This article investigated the use of three model selection information criteria—Akaike AIC, Schwarz SIC, and Bozdogan CAIC—for non-nested models. In general, SIC and CAIC were superior to AIC for relatively simple models, whereas AIC was superior for more complex models, although accuracy was often quite low for such models. In addition, some effects were detected for error rates in the models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(141 citation statements)
references
References 22 publications
8
133
0
Order By: Relevance
“…Recent simulation studies have found that Bayesian information criterion (BIC) typically underestimates the number of classes, while the Akaike information criterion (AIC) overestimates the number of classes [28,1], but that the AIC statistic generally outperforms the BIC statistic [5]. Table 2 presents both, as well as the AIC3, which Lin and Dayton ( [28] and Vermunt et al [60]) suggest as a good compromise in estimating the number of classes that should be represented in latent class analysis.…”
Section: First Stage Analysis: Cluster Derivationmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent simulation studies have found that Bayesian information criterion (BIC) typically underestimates the number of classes, while the Akaike information criterion (AIC) overestimates the number of classes [28,1], but that the AIC statistic generally outperforms the BIC statistic [5]. Table 2 presents both, as well as the AIC3, which Lin and Dayton ( [28] and Vermunt et al [60]) suggest as a good compromise in estimating the number of classes that should be represented in latent class analysis.…”
Section: First Stage Analysis: Cluster Derivationmentioning
confidence: 94%
“…Table 2 presents both, as well as the AIC3, which Lin and Dayton ( [28] and Vermunt et al [60]) suggest as a good compromise in estimating the number of classes that should be represented in latent class analysis. The BIC statistic is lowest for the two-cluster model (3991.03), while the AIC statistic is lowest for the five-cluster model (3874.92).…”
Section: First Stage Analysis: Cluster Derivationmentioning
confidence: 98%
“…These studies have generally suggested that BIC outperforms AIC, in that it often exhibits lower error rates and greater power. However, these studies have also generally concluded that neither criterion is completely satisfactory, and that other fit criteria exhibit greater power to select true models (Celeux and Soromenho, 1996;Lin and Dayton, 1997;Yang, 1998). Interestingly, Monte Carlo evidence suggests that early MDL approximations (Rissanen, 1978), essentially corrected forms of BIC, perform well in selecting latent class models (Yang, 1998).…”
Section: Previous Studies Of Information-theoretic Criteriamentioning
confidence: 95%
“…One limitation of both chi-square statistics is that they can only be used to compare nested models (Everitt 1988;Lin and Dayton 1997). Alternative methods are required for comparing models with a non-nested relationship.…”
Section: Assessing Model Fitmentioning
confidence: 98%